Transition of care for pediatric and adult patients with venous thromboembolism: A National Quality Improvement Project from the American Thrombosis and Hemostasis Network (ATHN). Issue 200 (April 2021) - DeSancho, M.; Munn, J.E.; Billett, H.H.; Cheng, D.; Holmes, C.; Jaffray, J.; Malone, M.; Patel, K.; Sharathkumar, A.; Thornburg, C.D.; Wang, M.; Watson, C.; et al.
Abstract: Background: Transition of care (TOC) for management of anticoagulation from inpatient to outpatient setting for patients with acute venous thromboembolism (VTE) poses serious safety concerns. We implemented a national quality improvement educational initiative to address this issue. Methods: Pediatric and adult patients admitted for their first VTE were prospectively enrolled at 16 centers from January 2016 to December 2018. Patient demographics, VTE diagnosis, risk factors, and treatment characteristics were collected. There were two phases: pre-intervention (PI) and quality intervention (QI). The PI phase assessed the quality and patient understanding and satisfaction of anticoagulation instructions given at hospital discharge and adherence to these instructions via a patient and/or caregiver feedback questionnaire (PFQ) and a patient knowledge questionnaire (PKQ) at 30 days. The QI phase provided patient and/or caregiver enhanced education regarding anticoagulation therapy and VTE at hospital discharge using a comprehensive discharge instruction module and a phone call follow-up at one week. Patient and/or caregiver knowledge at 7 and 30 days was assessed with the same PFQ and PKQ and compared to the PI baseline measures. Results: Of the 409 study patients, 210 (51%) were adults, 218 (53%) females, and 316 (77%) White. Deep vein thrombosis (62.8%) and pulmonary embolism (47.9%) were the most common VTE in children and adults, respectively. Day 30 PFQ scores were significantly higher in the QI phase compared to the PI phase by 11% ( p  < 0.01). Day 30 PKQ demonstrated enhanced teaching (93.7% vs. 83.5%, p -value 0.004) and disease recognition (89.6% vs. 84.6% p  = 0.03) in the QI phase than the PI phase. Conclusion: Comprehensive VTE discharge instructions followed by a 1-week post-discharge phone call strengthen patient and caregiver knowledge, satisfaction of education given and care provided, and disease recognition. Highlights: High quality transition of care (TOC) is vital for patients with venous thromboembolism (VTE) treated with anticoagulants. A multicenter quality improvement (QI) study was conducted in adult and pediatric patients diagnosed with their first VTE. Patient/caregiver knowledge at 7 and 30 days was assessed in the QI phase and compared to pre-intervention (PI) measures. The QI phase was associated with higher Day 30 scores (+ 11%) and greater teaching (+10%) and disease recognition (+5%). Systematic implementation of QI processes enhances knowledge of thrombosis and quality of TOC in patients with VTE.